From Martial Art to Stage Performance: Modern Adaptations of Kuntau Among the Dayak Iban - Claudia, Jiton; Juna, Liau; Dick Lembang, Dugun (UNIMAS Publisher, 2025)
This study explores the transformation of kuntau, a traditional martial art of the Iban Dayak community, from its origins as a martial art skill and symbol of male courage to its present role as a stage performance. The objective is to examine changes in function, community perception, and adjustments in practice and performance. Guided by a constructivist–interpretivist philosophy, the research employed a mixed approach involving a review of research questions with 122 respondents from Kuching, Samarahan, and Sri Aman, alongside field observations and in-depth interviews with five kuntau teachers. Findings indicate that while traditional elements such as floral movements, techniques, and symbolic values are preserved, modifications for stage performances have led to changes in movement patterns, reduced ritual practices, and increased choreographic features. Despite concerns over authenticity, the Iban community continues to regard kuntau as a significant and relevant cultural heritage. The discussion highlights the need to balance tradition with adaptation to contemporary contexts to ensure sustainability. This study contributes to the discourse on intangible cultural heritage preservation by providing insights into how cultural practices can evolve without losing their core identity.